CHILDHOOD SUBJECTIVITY AS A SITE OF CULTURAL RESILIENCE: DISPLACEMENT AND IDENTITY IN IBTISAM BARAKAT’S TASTING THE SKY - Thasneem S. K., Hanna; Mathew, Moncy (International Journal of Research -GRANTHAALAYAH, 2026)
This paper analyzes childhood subjectivity and the formation of resilient Palestinian identity in Ibtisam Barakat’s memoir, Tasting the Sky: A Palestinian Childhood (2007). The lens of Diaspora Theory and Deleuze and Guattari’s concept of the rhizome are used for the analysis of the work. This nonfiction, a memoir, recounts her own childhood experiences. The narrator of the novel is Ibtisam Barakat who memorizes her childhood in Palestine during the Six-Day War in 1967. Diverse recollections about childhood are revealed as this little girl attempts to confront the complexities of life, especially when the homeland is disrupted. The child is represented both as the observer and historical participant, who responds to displacement, which reveal about the mechanisms of identity construction in contexts of exile.These memories offer the narrator the opportunity to reclaim a part of her identity that was left behind in Palestine due to her migration to America. The analysis examines how the identity of the child narrator is rooted both in specific domestic and cultural practices, which included the sensory details of Palestinian life. By inscribing experience onto the child’s internal world, the memoir functions as both a personal and collective literary-political project. Tasting the Sky addresses history from a marginalized perspective, affirming cultural continuity, psychological healing, and a persistent claim to a lost home. The child’s identity, torn between a nostalgic past in Palestine and the reality of diaspora in America, becomes an act of resistance. Barakat’s memoir is transformed into a generative force for self-definition.